Meeting Needs with Scarce Resources: Community Network Building for Low-incidence Conditions - Judith A. Kahn; Georgianna Larson (Educational Considerations, 1989)
The development of a community network to improve services for children with chronic health conditions and their families takes planning, commitment, enthusiasm and interest.